Efecto de Arthrobacter agilis UMCV2, Trichoderma harzianum y dimetilhexadecilamina en la germinación y crecimiento de Pinus devoniana y Pinus greggii - Montejo Mayo, Wilber (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
The genus Pinus spp. includes approximately 110 species, of which around 50% live in Mexico. In many occasions the process of plant growth can be accelerated by the participation of soil microorganisms. The dimethylhexadecylamine is secreted by the Arthrobacter agilis UMCV2, has demonstrated the promotion of growth in plants as Medicago sativa and Medicago truncatula. In this work we have for objective to evaluate the effect of Arthrobacter agilis UMCV2, Trichoderma harzianum and dimethylhexadecylamine in germination and growth of Pinus Devonian and Pinus greggii. The seed of Pinus greggii and Pinus Devonian and were placed in Petri dishes in bacteriological agar, which was complimented with dimethylhexadecylamine to concentrations: 0, 1, 10, 20 and 30 μM. The treatments with microorganisms were soaked the seeds with cells from A. agilis UMCV2 and in co-action T. harzianum were placed on agar bacteriological. The results show us that to 10 μM promotes germination of P. Devonian in 72% and treatment with bacteria introduced greater length radículas. The 1 μM concentration promotes germination of P. greggii 65%. In another experiment that was to apply dimethylhexadecylamine, A. agilis UMCV2 and T. harazianum in a system where the plants grow in substrate sterile and non-sterile added as irrigation water. Resulting after a period of 240 days of exposure with the organisms we find a greater growth in the plants of P. Devonian in sterile substrate reflected in length of the aerial part, fresh and dry weight of the root. In conclusion the dimethylhexadecylamine at low concentrations promotes germination of the seeds of P. Devonian and P. greggii. The rizobactreria A. agilis UMCV2 and in co-action with T. harzianum promotes the growth of plants only P. Devonian.

El género Pinus spp. incluye aproximadamente 110 especies, de las cuales alrededor del 50% habitan en México. En muchas ocasiones el proceso de crecimiento vegetal puede ser acelerado por la participación de microorganismos del suelo. La dimetilhexadecilamina es secretada por la rizobacteria Arthrobacter agilis UMCV2, ha demostrado promover el crecimiento en plantas como Medicago sativa y Medicago truncatula. En este trabajo tenemos por objetivo evaluar el efecto de Arthrobacter agilis UMCV2, Trichoderma harzianum y dimetilhexadecilamina en la germinación y crecimiento de Pinus devoniana y Pinus greggii. Las semillas de Pinus devoniana y Pinus greggii fueron colocadas en cajas de Petri en medio Agar bacteriológico, el cual fue adicionado con dimetilhexadecilamina a concentraciones: Cero, 1, 10, 20 y 30 μM. Los tratamientos con microorganismos se remojaron las semillas con las células de A. agilis UMCV2 y en co-accion T. harzianum se colocaron en agar bacteriológico. Los resultados nos muestran que a 10μM promueve la germinación de P. devoniana en un 72% y el tratamiento con bacteria presento mayor longitud de radículas. La concentración 1 μM promueve la germinación de P. greggii 65%. En otro experimento que consistió en aplicar dimetilhexadecilamina, A. agilis UMCV2 y T. harazianum en un sistema donde las plantas crecieran en sustrato estéril y no estéril adicionada como agua de riego. Resultando después de un periodo de 240 días de exposición con los microorganismos encontramos mayor crecimiento en las plantas de P. devoniana en sustrato estéril reflejado en longitud de la parte aérea, peso fresco y seco de la raíz. En conclusión la dimetilhexadecilamina a concentraciones bajas promueve la germinación de las semillas de P. devoniana y P. greggii. La rizobactreria A. agilis UMCV2 y en co-accion con T. harzianum promueve el crecimiento solamente las plantas de P. devoniana.
Facultad de Ingeniería en Tecnología de la Madera. Maestría en Ciencias en Tecnología de la Madera
Keywords: info:eu-repo/classification/cti/7; FITECMA-M-2015-0488; Arthobacter agilis; Dimetilhexadecilamina; Trichoderma harzianum; Pinus devoniana; Pinus reggii; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/203